Development of saba figs (Compresa blanco teodora) - Penafiel, Ma. Alita G.; De Leon, Sonia Y. (1982.)
In this study, frying treatment of Saba banana (Compresa blanco teodora) were evaluated. Comparison was made between the Saba figs developed in this study, and the Cavendish figs developed in UP-NSDB Project 7901, by Corpus and de Leon, 1979, as to preference, color and texture. Three drying pretreatments for Saba figs namely: first, sulfiting the bananas for 20 minutes in 1% sodium metabisulfite; second, blanching them for 3 minutes in boiling water with their peels on, third, blanching then sulfiting them, were tested together with the control. They were all dried initially for 10 hours at 140°F in a cabinet dryer, sealed in tight plastic jars overnight, then dried again for 8 hours at 140°F in the same drier, as the drying of Cavendish figs. Under the condition of Phase 1 of this experiment, it was found that the drying pretreatment could be omitted. Control was evaluated by the panelists as plump in shape, while the rest were evaluated as mushy to plump. It scored highest in shape and was significantly different from the rest in this attribute. For color, control and sulfited were evaluated as having golden brown color, while blanched and blanched then sulfited were evaluated as darkened. The first 2 obtained higher scores than the latter 2 in color. Control and sulfited were not significantly different in from each other, but significantly different from blanched and blanched then sulfited. The colored photograph of the samples showed, however, that all the samples were uneven golden brown in odor. For flavor/odor, the 4 samples were evaluated as just having recognizable banana flavor/odor to having slight banana flavor/odor. No significant difference occurred in flavor/odor among the 4. For texture, the samples were evaluated as being very tender to tender. No significant differences occurred in texture among the 4. There were comments, however, that the texture was tough and the samples had case-hardened. These comments were supported by the moisture determination and penetrometer readings on the 4 samples. Their moisture ranged from 12.5 to 13.5% (wet basis) which was lower than the 15 to 18% moisture content suggested for banana figs. The penetrometer readings of the 4 samples which ranged from 0.04 to 0.56 mm were lower than that of 1.88 mm penetrometer reading of Cavendish figs. For acceptability no significant differences occurred among the 4 samples, and they were evaluated to being neither liked nor disliked to being slightly liked. In Phase 2 of the study it was found that Cavendish figs were preferable than the Saba figs developed. The mean score for the degree of preference approximated that of moderate. The Cavendish figs had a more superior uniform brown color than Saba figs, which had uneven golden brown color having parts that were pale. The Cavendish figs were softer in texture than Saba figs, which gained comments earlier that they were tough in texture. The moisture content of Cavendish figs which was 17.6% was higher than the 13.5% moisture content of Saba figs. The 1.88 mm penetrometer reading of Cavendish figs, as compared to the 0.56 mm obtained from Saba figs also showed the superiority of the former to the latter, in texture.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Bananas